Performance of Emergency Department Nurses During Cardiopulmonary Resuscitation and its Relationship with Professional Value and Job Satisfaction - Fatemeh Mahmoodjanlu; Ali Hesamzadeh; Mahmood Moosazadeh; Vida Shafipour (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: The tensions in the emergency department can affect job satisfaction and professional values of nurses working in this department which may influence their clinical performance. The present study investigated the performance of emergency department nurses during cardiopulmonary resuscitation (CPR) and its association with professional value and job satisfaction. Materials and methods: This cross-sectional study was conducted in 10 hospitals affiliated to Mazandaran University of Medical Sciences in 2020-2021. The study samples were 258 nurses in emergency department selected via convenience sampling and quota based on the number of emergency department personnel in every hospital. Data were collected using demographic questionnaire, self-performance checklist in CPR, The Minnesota Satisfaction Questionnaire (MSQ), and The Nurses Professional Values Scale--Revised (NPVS-R). Data analysis was carried out in SPSS V22. Results: The majority of samples (71.7%) were women and the mean age of participants was 31.09±4.7 years. The overall mean scores for professional value, job satisfaction, and nurses' self-performance in CPR were 100.49±14.7, 56.34±12.7, and 30.84±3.0, respectively. Weak direct correlation coefficients were found between nurses' job satisfaction and their performance (r=0.201, P=0.001) and professional values (r=0.339, P=0.001), and also between their professional values and performance (r=0.374, P=0.001). Conclusion: In this study, direct relationships were found between the performance of emergency department nurses in CPR and professional values and job satisfaction. Measures should be taken so that nurses get more familiar with different dimensions of nursing professional values and internalize these values in a wide range of nursing affairs, thereby having higher job satisfaction and clinical performance.